STUDI ANALISIS AYAT-AYAT WAKAF DALAM TAFSIR AL-AZHAR - Achmad Dzikri Rajuli; Didin Hafidhuddin; Hendri Tanjung (Kasaba, 2020)
The basic reason why does the writer choose this title is because of the writer is so interested in Buya Hamka’s Interpretation of Ali Imran Surah: 92. Buya Hamka in this Interpretation was giving an example of Waqf practice by the Dzurry (Waqf Expert). It’s has been done by the prophet Muhammad’s friend. The pointed focus of this thesis is want to know which one is the verse of Al-qur’an that explained about waqf especially, about “How to Interpretate?” and “How to Identify” the waqf, and the last one is what the Buya Hamka opinion about it? The method of this thesis is a quality method (library research) through al-Azhar translation by Buya Hamka. Beside by add the literate, the writer using other waqf books as references. The result that there is two surahs that support the waqf. They are Surah Al-Baqarah ayah 177, 26, 267 and Surah Ali Imran ayah 92, 133,134, Buya Hamka told that there are two kinds of waqf; they are Dzurry Waqf and Khairy Waqf. From both of them, waqf can be the same meaning of shodaqoh, which means shodaqoh thatawwu (man charity). Shodaqoh thatawwu the shodaqoh that some one who wants to giving their property, they can give it in any time and any where. They give it without any time limitation and without discrimination (indiscriminate) even they rich or poor. Finally, the people who are giving waqf (waqif) will receive their akhirat reward until they died, as long as the goods are represented for many kindnesses.